Originally Posted by

**Nappy** When asked to prove that x = -1 is a solution to the equation

x2 + 3x + 2 = 0

my lecturer told us that substituting the x = -1 into the equation was not enough as we are assuming we have a solution rather than proving x = -1 was. This confused me.

He went on to show us how to do it which involved subbing in another variable for x say x = x0 and letting the RHS=LHS. To me this was exactly the same as what he had told us not to do which further confused me. So question 1 how can I prove x = -1 is a solution to the above equation.

Cheers

Nappy